Depressive symptoms, but not anxiety, predict subsequent diagnosis of Coronavirus disease 19: a national cohort study. (25th March 2022) - Meinlschmidt, G.; Guemghar, S.; Roemmel, N.; Battegay, E.; Hunziker, S.; Schaefert, R.
Abstract: Aims: Several diseases are linked to increased risk of Coronavirus disease 19 (COVID-19). Our aim was to investigate whether depressive and anxiety symptoms predict subsequent risk of COVID-19, as has been shown for other respiratory infections. Methods: We based our analysis on UK Biobank participants providing prospective data to estimate temporal association between depressive and anxiety symptoms and COVID-19. We estimated whether the magnitude of these symptoms predicts subsequent diagnosis of COVID-19 in this sample. Further, we evaluated whether depressive and anxiety symptoms predicted (i) being tested for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and (ii) COVID-19 in those tested. Results: Based on data from N = 135 102 participants, depressive symptoms (odds ratio (OR) = 1.052; 95% confidence interval (CI) 1.017–1.086; absolute case risk: (moderately) severe depression: 493 per 100 000 v . minimal depression: 231 per 100 000) but not anxiety (OR = 1.009; 95% CI 0.97–1.047) predicted COVID-19. While depressive symptoms but not anxiety predicted (i) being tested for SARS-CoV-2 (OR = 1.039; 95% CI 1.029–1.05 and OR = 0.99; 95% CI 0.978–1.002), (ii) neither predicted COVID-19 in those tested (OR = 1.015; 95% CI 0.981–1.05 and OR = 1.021; 95% CI 0.981–1.061). Results remained stable after adjusting for sociodemographic characteristics, multimorbidity and behavioural factors. Conclusions: Depressive symptoms were associated with a higher risk of COVID-19 diagnosis, irrespective of multimorbidities. Potential underlying mechanisms to be elucidated include risk behaviour, symptom perception, healthcare use, testing likelihood, viral exposure, immune function and disease progress. Our findings highlight the relevance of mental processes in the context of COVID-19.